Proceedings of the Oklahoma Academy of Science - Oklahoma Academy of Science; University of Oklahoma; Oklahoma Junior Academy of Science (University studies series, 1920)
Vols. 1-49 are Proceedings of the 1st-57th annual meetings.
Keywords: Science : Periodicals; Science